«Come l’ombra accompagna la nube». Alcune riflessioni sull’iconografia di Ettore in duello nella ceramica attica - Dario D'Orlando; Federica Doria (Otium, 2016)
This work focuses on the character of Hector, son of the king of Troy Priam, and his iconographical traduction in Athenian figurated pottery. Even if the Trojan warrior is a marginal figure in 6th and 5th centuries BC in Greece, his presence in the representation of all the various stages of a warrior’s life makes him an useful tool in the costruction of the idea of hero and soldier. Probably for this reason many vases show duels between Hector and the argives heroes like Ajax and Achilles. Unlike the superficial interpretation of these images, the authors try to propose new iconological keys. In fact, reading the scenes of the duel between Hector and Ajax, is explained the link with the future death of both. Otherwise in the images in which the Trojan prince faces Achilles the key is put on the iconographical figure of Hector as a defeated hero.